The referral pattern of patients to periodontists by general dentists - Vaziri, Farzane; Zarifpour, Lina (Brazilian Dental Science, 2022)
Objective: The successful periodontal therapy needs a proper relationship between general dentist and periodontist.The aim of this study was to determine the referral pattern of patients to periodontists by general dentists in Yazd,Iran, by means of a questionnaire. Material and Methods: This descriptive cross-sectional study was carried out inthe form of a survey among 145 licensed general dental practitioners in Yazd, Iran. A questionnaire comprising ofseven questions with sub-questions was prepared. Results: 89% of dentists have referred patient to periodontist.Gingival recession was the most frequent reason for referring (69.7%) and the least was gingival bleeding (13.1%).The most frequent surgical procedure for what patients have been referred were peri-implantitis therapy and ridgeaugmentation. Referral status to periodontist for female dentists was 95.9% and for male dentists was 81.7%. Thenumber of referred patients form the dentists who were practicing simultaneously at both private and public clinicswas higher than those who were practicing only at private or public clinics. The most referral percentage was inthe group of dentists with less than 5 years of experience with a slight difference from those with more than 10years of experience. Only 26.1% of the respondents have participated in retraining programs. Conclusion: Thereis a need for general dentists to consider the primary signs of periodontal disease and necessity of referring thepatients in early stages more serious, to provide an optimal long-term outcome for patients.KEYWORDSDentist; Periodontal disease; Referral.